The Concept of Relationship Between Debt and Receivable: Evidence on Basic Industrial Companies in Indonesia - Darmawan Darmawan; Achmad Jufri (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
The study's purpose was to determine whether there is a two-way influence between debt and receivables, the response of a variable to sShocks that occur in other variables and the contribution of each variable to other variables. Debt and receivable data are taken from 48 of the 91 companies in the basic industrial sector listed on the IDX. The statistical model used in this study is the Vector Autoregression Model, which aims to test the direction of influence between two variables. The results show that debt affects receivables, while accounts receivable do not affect debt. So there is only a one-way relationship between debt to receivables. This finding reinforced that the debt response to the shock in receivables did not find a significant response. Meanwhile, the response of receivables variable shock to itself since period 1 has fluctuated and has been stable since period 6. The receivables response to the shock in debt began to respond in the second period and was stable from period 6. The contribution of the receivable variable to itself had a negative trend. In contrast, the contribution of the variable debt to receivables shows a positive direction.